The Risk Assessment of Oxidative Stress in Postpartum Dairy Cattle - Yu, Hongyi; Zhang, Cuiyu; Qian, Weidong; Zhao, Chang; Zhang, Hongyou; Xia, Cheng (Acta Scientiae Veterinariae, 2020)
Background: Negative energy balance in cows will induce catabolism especially of lipids and the resulting rapid increase of free fatty acids (NEFA) in the blood stream increases the production of reactive oxygen metabolites (ROMs) and promote oxidative stress. Once the animal body is in an oxidative stress state, many molecules in the body may be peroxidized, accelerating the destruction of cells and causing damage to tissues or organs. This study conducted risk assessment of the oxidative stress caused by negative postpartum energy balance in cows by exploring the relationship between negative energy balance and oxidative stress. Materials, Methods & Results: This experiment randomly selected 120 cows at 14 to 21 days postpartum, from an intensive cattle farm in Heilongjiang province, China. Using a negative energy balance standard of β-hydroxybutyric acid (BHBA) greater than 1.2 mmol/L, <a href="https://www.so.com/link?m=aWo9Notwgv2355DY/andwkFHdhfyKBhSzW00Sx+vmFsnKezsD8IIts3YgX50kLnFE7vdQB7F3gRSNTsFARWz1mO4oGD3jk3FLEr6B6PZIbuueK//LoAkIvJKqCHE9D/SLFL84KlPKapQeHUG196iiG4B2lHqwUCSNzVxLlJ4W8rI=" target="https://www.so.com/_blank">nonesterified fatty acid (NEFA) greater than 0.4 mmol/L and glucose (GLU) less than three mmol/L, the cattle were divided into a healthy group of 74 cows and a diseased group of 46 cows. The oxidative stress indices of the experimental cows were measured and analyzed using the independent sample t test. Spearman correlation analysis and regression analysis were performed and by using the binary Logistic regression analysis to predict disease, the receiver-operating characteristic curve (ROC) analysis established diagnosis effect and boundary values. Compared with the healthy group, the levels of glutathione peroxidase (GSH-Px), catalase (CAT), vitamin E (VE), selenium (Se) and total nitric oxide synthetase (T-NOS) in the blood of dairy cows in the diseased group were significantly reduced and the level of malondialdehyde (MDA) was significantly increased. The study concluded that negative energy balance is associated with oxidative stress in cows and the blood levels of GSH-Px, CAT and Se can be used to evaluate the degree of resulting oxidative stress. The early warning levels were determined to be GSH-Px less than 619.28 U/L, CAT less than 7.87 U/ml and Se less than 0.51 μg/L. Discussion: The levels of GSH-Px, CAT, Se, T-NOS and VE in the blood of cows in the disease group were lower than those in the healthy control group. This may be due to the increase in energy demand of cows in the perinatal period and the decrease of DMI in this period, which promotes the NEB of cows. In order to alleviate the NEB, the body forces its metabolic enhancement. Some tissues of the body cannot adjust their metabolism to adapt to NEB and this leads to excessive NEFA, which causes oxidative stress. Excessive NEFA can also affect the expression of GSH-Px in cells, and causing a series of oxidation reactions, increased free radicals and as the antioxidant system is overwhelmed. The MDA content in the blood of the deficient group was significantly increased compared with the healthy group, positively correlated with NEFA and BHBA and negatively correlated with GLU. This may be due to severe oxidative stress in cows during the period of negative energy balance as MDA is one of the important products of membrane lipid peroxidation. Long chain PUFA are an important component of all cell membranes and their oxidation damages the integrity, fluidity and function of cell membranes. In summary MDA causes oxidative damage to cells, damages mitochondrial membranes and changes membrane permeability, resulting in more free radicals produced by mitochondria during biological oxidation.